Uncovering a new route to pain therapy. (September 2022) - Ren, Xiangyu; Zhang, Han-Xiong Bear
Highlights: Adeno-associated virus (AAV)-delivered Cav ∝βlator results in a remarkable ubiquitination and ablation of high voltage-activated calcium channels (HVACCs) in the primary sensory neurons. Ablation of HVACCs and calcium current in the primary sensory neurons significantly reduces neuronal excitability and neurotransmitter release. Loss of HVACCs in the sensory neurons also alters the inhibitory inputs to the "pain-transmission" neurons in the spinal dorsal horn. Subcutaneous application of Cav ∝βlator provides a novel method for alleviating chronic pain sensation caused by nerve injury. Abstract: High-voltage-activated calcium channels (HVACCs) are promising targets for developing analgesics given their roles in controlling synaptic transmission, neuronal excitability and neuropeptide release in primary nociceptive neurons. Despite previous efforts in developing HVACCs inhibitors of various drug modalities, it remains undetermined whether targeting HVACCs directly by a gene therapy approach could lead to pain alleviation in vivo. To test this, Sun and colleagues adopted a post-translational ubiquitination-based knockdown method targeting HVACCs in primary sensory neurons. They showed ablation of HVACC currents in a subset of primary sensory neurons, dampened hyperexcitability of sensory neurons after nerve injury and reduced pain behavior with no apparent adverse effects [1] . The results open the possibility of targeting ion channels with ubiquitination-based knockdown as a promising gene therapy candidate for pain treatment in future clinical studies. Graphical abstract: Image, graphical abstract